MENENTUKAN PRODUKSI ENERGI (kWh) PADA PERENCANAAN PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO (PLTMH) SUNGAI AEK SILANG di KABUPATEN HUMBANG HASUNDUTAN - Lumban Gaol, Partahi; Simanjuntak, Salomo (Jurnal Visi Eksakta, 2020)
This study concerned with designing a micro hydro power generation. The capacity of the plant is calculated on the basis of dependable flow, namely the amount of discharge that is equalled or exceeded during a certain period or with certain probability. Large designed flow have low probability of occurence. Small designed flow is more likely to occur but only produce little electrical power. Designed flow has big influence to production cost of each kWh of power generated. In this study, optimum designed flow is obtained through optimisation of parameter such as cost of producing 1 kWh power from several value of dependable flow. This study conclude that an optimum economic value can be reached by dependable flow of 8,165 m3/s with 45% probability. The cost of producing the power is Rp 557.54 per kWh. The plant generates approximately 64.530.792,94 kWh electrical power in one year.